Neglected Spaces in Peripheral Places : Homeworkers and the Creation of a New Economic Centre - Mackenzie, Suzanne (Cahiers de géographie du Québec, 1987)
This paper suggests that the current recession and restructuring may be creating new centres of economic and social innovation, the analytically and politically neglected homes and communities in the "peripheral" regions of Canada. Using data from the West Kootenay area of British Columbia, it is argued that people are responding to declining employment opportunities by utilizing the resources remaining to them in their homes and communities to develop new survival strategies. The paper focusses on home based businesses and cooperative networks in two fields — childeare and craft manufacture — which have been established primarily by women. These businesses and networks are assessed in terms of their mobilization of local resources and their impact on the economic and social life of the region. It is argued that, despite serious shortcomings, these may provide indications of new gender relations, based on family or household partnerships, and new economic relations, based on meeting local needs rather than the profitability requirements of corporations.